Catalytic Asymmetric Total Syntheses of (+)- and (−)-ar-Elvirol Methyl Ether - Mondal, Debabrata; Patel, Dhruvilkumar Sureshkumar; Bisai, Vishnumaya (Synlett, 2025)
A catalytic asymmetric approach to either of the enantiomers of naturally occurring sesquiterpenes, i.e., (+)-ar-elvirol (1a) and (−)-ar-elvirol (ent-1a), has been achieved via a reductive transposition of a tertiary alcohol following a key allylic diazene arrangement (ADR) from an advanced enantioenriched tertiary allyl alcohol. The ADR proceeds via the reductive transposition of olefin under the Mitsunobu reaction with o-nitro benzene sulfonyl hydrazide followed by the decomposition of the sulfonyl hydrazide adduct. This approach has been utilized for the total syntheses of bisabolene sesquiterpenoids, (+)-ar-elvirol methyl ether (1b) and (−)-ar-elvirol methyl ether (ent-1b).
Keywords: Allylic diazene rearrangement (ADR); Asymmetric conjugate addition; Aromatic bisabolanes; E-Ethyl crotonate; Boronic acid; (+)-ar-Elvirol (1a); (+)-ar-Elvirol methyl ether (1b)